Exercise overcome adverse effects among prostate cancer patients receiving androgen deprivation therapy: An update meta-analysis. Issue 27 (July 2017) - Yunfeng, Gao; Weiyang, He; Xueyang, He; Yilong, Huang; Xin, Gou
Abstract: Background: Prostate cancer (PCa) patients initiating androgen deprivation therapy (ADT) are suffering from adverse effects; exercise has been proposed as a treatment to relieve adverse effects of ADT, available meta-analysis has proved exercise improves quality of life, and therapy caused fatigue; recently, some high-quality trials have been conducted in order to get more assessment; we conduct an updated meta-analysis to evaluate feasibility that exercise relieves adverse effects in PCa patients initiating ADT. Materials and methods: A systematic article search was performed from Cochrane Library, MEDLINE, EMBASE, and PubMed databases up to March 10, 2017. Outcomes included changes in body composition, physical function, bone health and cardiometabolic changes. We conduct subgroup analysis to analyze the duration and type of exercise correlated with the effect and calculated using standard mean difference (SMD) and corresponding 95% confidence intervals (CI). Result: Fifteen studies involving 1135 patients were included in our meta-analysis, and significant positive effects were found in body strength (leg press (SMD: 0.78 (95%CI: 0.57–0.99, P <.00001, I 2 = 0%)), chest press (SMD: 0.71 (95%CI: 0.50–0.92, P <.00001, I 2 = 0%)), exercise tolerance (VO2 peak SMD: 0.35 (95%CI: 0.04–0.66, P = .03, I 2 = 0%) in 6 months and SMD: 0.59 (95%CI: 0.16–1.03, P = .007, I 2 = 0% over 6 months)), fatigue (SMD: 0.84 (95%CI: −1.43 to 3.10, P = .85, I 2 = 51%) in 6 months and SMD: −9.3 (95%CI: −16.22 to −2.39, P = .0030, I 2 = 49%) over 6 months)), ADT-caused obesity (body mass index SMD: −0.33 (95%CI: −0.55 to −0.12, P = .002, I 2 = 38% in 6 months and SMD: −0.59 95%CI: −1.02 to 0.17, P = .006, I 2 = 25% over 6 months)), and sex function (SMD: 0.66 (95%CI: 0.35–0.97, P <.00001, I 2 = 2%). There were no evidence of benefit for cardiometabolic changes and bone health. No systematic difference was observed between resistance exercise training (RET) and aerobic exercise training (AET) in ADT-caused obesity, fatigue, and exercise tolerance Conclusion: Exercise can significantly improve the upper and lower muscle strength, increase exercise tolerance, help PCa patients receiving ADT control their body fat mass, BMI, and keep the sex function. ADT-related fatigue is correlated with exercise duration time. No differences were observed in LBM, bone mineral density, and any other metabolic blood markers. Available data show that there is no difference between AET and RET.